Experimental Study to Develop a Method for Improving Sample Collection to Monitor Laryngoscopes after Reprocessing - Savina Ditommaso; Monica Giacomuzzi; Elisa Ricciardi; Carla Zotti (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims The microbiological surveillance of endoscopes and automated flexible endoscope reprocessing have been proven to be two of the most difficult and controversial areas of infection control in endoscopy. The purpose of this study was to standardize a sampling method for assessing the effectiveness of standard reprocessing operating procedures for flexible fiberoptic laryngoscopes (FFLs). Methods First, the sampling devices were directly inoculated with Bacillus atrophaeus spores; second, tissue non tissue (TNT) wipes were tested on artificially contaminated surfaces and on FFLs. Results Comparison of the sponges, cellulose, and TNT wipes indicated that the TNT wipes were more effective in releasing spores (93%) than the sponges (49%) and cellulose wipes (52%). The developed protocol provides a high efficiency for both collection and extraction from the stainless steel surface (87% of the spores were removed and released) and from the FFL (85% of the spores were removed and released), with relatively low standard deviations for recovery efficiency, particularly for the analysis of the FFL. Conclusions TNT wipes are more efficient for sampling surface areas, thereby aiding in the accuracy and reproducibility of environmental surveillance.